Hybrid coupling method to nonlinear acoustic source and linear duct system using parameter identification of the input impedance in fluid machinery. (17th March 2016) - Oh, Seungjae; Wang, Semyung; Cho, Sungman
Abstract: The acoustic source in fluid machinery is described as nonlinear. However, acoustic wave propagation in the muffler is represented by a linear system. Therefore, the acoustic source is modeled in the time domain, and the acoustic propagation is expressed in the frequency domain. The method of analyzing the acoustic in different domains is known as hybrid coupling. In this paper, a developed non-iterative hybrid coupling method was suggested, where the parameter identification using the rational fractional polynomial method is performed with the measured input impedance of the muffler described in the frequency domain. In this case, the relationship of the polynomial order of the denominator and numerator was determined from the analogy of a mechanical system. The approximated input impedance model is transformed to the state space model, which is described in the time domain. Finally, this model is coupled to a nonlinear acoustic source to analyze in the time domain. The proposed method can be used in more diverse condition than the other method. Simultaneously, a transient response can be obtained. The proposed method was experimentally verified using the suction part of a linear compressor, which is representative of fluid machinery. Highlights: Suggesting the parameter identification method of the input impedance Applying the multi-DOF experimental modal analysis based on the rational function Determining the relationship polynomial order of the denominator and numerator Validating the proposed method using the suction part of a linear compressor